Relatório de Estágio Profissional "No Caminho da docência: de aluno a professor" - Adolfo Ricardo Gonçalves de Sá (2017)
This report marks the conclusion of the formation process to which the student is submitted to achieve the master degree in teaching physical education in basic and secondary education. So, the focus of the document is about the course of the professional internship, moment in which the student contacts with the reality of teaching and realizes the difficulties inherent in its practice, looking for the overcoming spirit and the development of skills and competences required to its practice. Therefore, the following pages constitute a description of the difficulties and achievements experienced throughout the year and the most defining moments of this stage and of my work as a student. Theory and practice are viewed hereby with a reflective process that unites them and gives meaning to my definition of being a "good teacher". In shearch of continuous learning this written has even a study centered on the use of the Sport Education Model throughout the second period, where I pretend to take conclusions about the perception of the students in that. A summary of the course of the professional internship is presents furthermore, where its also exposed my expectations against the professional future, for as life is made by periods, this goal means to me "the end of the beginning".